Currency boards: In theory and in modern -day practice - Ho, Corrinne Miu-ching (ProQuest Dissertations & Theses, 2002)
Long considered to be an unfashionable relic of colonialism, currency boards made a comeback in the late 1980s and early 1990s as an alternative, and often controversial, rule-based monetary framework. This dissertation, Currency boards: in theory and in modern-day practice, examines various issues that arise in the discussions and practice of “second generation” currency boards. It consists of three chapters: Chapter I, To Kill a Currency Board: Soroi not Necessary, is a theoretical investigation of crises in the context of a currency board regime. It develops a model that explores the conditions under which a properly-run currency board can be subject to attacks and collapse. It highlights how the outcome depends on the strength of the banking system, the preferences of the authorities and the perceptions of agents. It also examines the connection between the strength (both intrinsic and actual) and the credibility of the regime. Chapter II, Contemplating the Credibility of Currency Boards , is an essay on some observations on the issue of “credibility” in modern-day currency board regimes. It picks up some of the conclusions in the theoretical chapter to see how they play out in practice. In particular, it highlights the role of context and circumstances in the determination of “credibility-worthiness” and “credibility.” Chapter III, The Institutional and Operational Aspects of Modern-day Currency Boards, surveys the organization and design, operations and legal foundations the six modern currency boards. While Chapter I speaks of currency boards in a stylized sense and Chapter II highlights the role of less tangible factors, this final chapter focuses squarely on the very tangible and practical aspects. It explores how and why modern currency boards are necessarily different from the classic/“orthodox” blueprint and the implications thereof.